Closing the gender gap in farming under climate chnage - Huyer, Sophia (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2017)
Presented by Sophia Huyer on 30 May 2017, as part of the webinar 'Gender, climate change and agriculture'. The webinar was co-organized by the CGIAR Collaborative Platform for Gender Research and the CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS).